Kreativitas dalam Pembelajaran Sejarah Abadke-21 Studi Kasus di Sma Negeri 2 Wonogiri - Anggoro Bimo Putranto; Djono Djono (Universitas Galuh, 2026)
This study critically analyzes the conceptualization and implementation of creativity in 21st-century history education under the Kurikulum Merdeka framework. Employing a qualitative case study with a socio-constructivist perspective, data were gathered via interviews, observations, and document analysis, then processed using Miles and Huberman’s thematic analysis. The results indicate that creativity in history is a socially mediated process shaped by pedagogical design, student characteristics, and structural constraints. Furthermore, a tension exists between curriculum policy and classroom reality. The study’s novelty lies in the development of